2017
DOI: 10.1117/1.jbo.22.10.105004
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive detection of nasopharyngeal carcinoma based on saliva proteins using surface-enhanced Raman spectroscopy

Abstract: The present study evaluated the capability of saliva analysis combining membrane protein purification with surface-enhanced Raman spectroscopy (SERS) for noninvasive detection of nasopharyngeal carcinoma (NPC). A rapid and convenient protein purification method based on cellulose acetate membrane was developed. A total of 659 high-quality SERS spectra were acquired from purified proteins extracted from the saliva samples of 170 patients with pathologically confirmed NPC and 71 healthy volunteers. Spectral anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…However, conventional ORPAMs, employing mechanical raster scanning of optical and acoustic focuses, suffer from a low imaging speed and translation of samples/imaging interfaces . Recent progress in new acoustic/optical scanning mechanisms and ultrafast pulsed lasers promotes the development of high‐speed and compact ORPAMs . One encouraging approach introduces water‐immersed magnetic micro‐mirrors capable of scanning both optical and acoustic focuses to achieve portable configurations of ORPAM .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conventional ORPAMs, employing mechanical raster scanning of optical and acoustic focuses, suffer from a low imaging speed and translation of samples/imaging interfaces . Recent progress in new acoustic/optical scanning mechanisms and ultrafast pulsed lasers promotes the development of high‐speed and compact ORPAMs . One encouraging approach introduces water‐immersed magnetic micro‐mirrors capable of scanning both optical and acoustic focuses to achieve portable configurations of ORPAM .…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in new acoustic/optical scanning mechanisms and ultrafast pulsed lasers promotes the development of high‐speed and compact ORPAMs . One encouraging approach introduces water‐immersed magnetic micro‐mirrors capable of scanning both optical and acoustic focuses to achieve portable configurations of ORPAM . Another study integrates an imaging bundle and a graded‐index lens to realize a miniaturized handheld ORPAM probe .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to improve the diagnostic performance of the urinary modified nucleosides SERS, we fully utilize all the diagnostically significant information contained in the SERS spectra of urinary modified nucleosides by implementing a PCA‐LDA multivariate statistical analysis for diagnostic model development. These diagnostic algorithms have been widely utilized by researchers for cancer tissue, blood, cell and saliva detection . In this study, PCA‐LDA analysis demonstrates good diagnostic performances of the urinary modified nucleosides SERS spectroscopy for detection of gastric cancer and breast cancer, as shown in Figure A–C.…”
Section: Discussionmentioning
confidence: 78%
“…In 2017, the same group, Lin X. et al, published another report, with a bigger cohort (170 patients with nasopharyngeal carcinoma and 71 controls) [ 18 ]. Moreover, the spectral analysis was performed on the purified saliva proteins, and the rest of the protocol remained strictly identical.…”
Section: Resultsmentioning
confidence: 99%
“…However, for blood sampling, it has been shown that storage at −80 °C and in plastic tubes has no effect on generated spectra, whereas variations in the drying and the storage of samples (fresh or frozen, avoid freeze-thaw cycles) can have an effect [ 49 ]. Therefore, standardization of saliva sample handling (collection, processing, and storage protocols) is crucial to ensure reproducibility and consistency in the results obtained as suggested by other reports [ 4 , 18 , 50 ].…”
Section: Discussionmentioning
confidence: 99%